Maternity and Child Welfare
1928 1928 1920s 5 pages West Riding scheme numbered 1,877. There are 13 School Clinics and 73 combined Child Welfare Centres and School Clinics, 101 whole-time and 70 part-time School Nurses (who also act as Health Visitors), and 6 whole-time School Nurses. The following is a summary of the work done during the year :- Visits to Schools by the Nurses 7,180 Visits to homes by the Nurses 30,981 Number of minor ailments treated by Nurses at own homes or School Clinics 48,019 Treatment of defects of nose and throat (2304 under the West Riding Scheme in Clinic or Hospital). 4,427 TREATMENT OF VENEREAL DISEASES. Facilities for the diagnosis and treatment of Venereal Diseases on the most modern lines are provided all over the Riding, agreements being made with the County Boroughs, and where the distance is too great to attend at these places Clinics have been opened by the County Council at suitable centres. The Medical Officer of Health in each area is aware of these facilities and can give all necessary information. The Clinics in the West Riding number seventeen, and hours of attendance have been arranged to suit the particular industry in the neighbourhood. Any enquiries to the County Medical Officer will be treated as confidential, and given prompt attention. 292/824/1/120